Meningkatkan Motivasi Dan Hasil Belajar Siswa Tentang Sains Melalui Penggunaan Strategi Inkuiri Terbimbing Di Kelas VI SDN 15 Palu - I Nyoman Setiartawan; Amiruddin Kade; Lilies N. Tangge (Mitra Sains, 2015)
This study aimed to describe the students' motivation during the implementation of guided inquiry strategy onlearning of Science, and to describe improving learning achievement of students after the implementation of guided inquiry strategy on learning of Science in the Class VI at SDN 15 Palu, The method used was the classroom action research, implemented at SDN 15 Palu school year 2014/2015 in the Class VI consisted of 26 students. This study was conducted over two cycles. Each cycle included of planning, implementation, observation, and reflection. Data were qualitative collected through observation techniques, and quantitative obtained by giving a test at the end of each cycle. Results of the study showed that the implementation of guided inquiry strategy improved effectively learning achievement of students in the Class VI at SDN 15 Palu. Improving learning achievement was demonstrated by the acquisition of their learning achievement sat the first cycle as follows: the percentage of individual absorption was good average, the percentage of classical completeness was good average, and the percentage of classical absorption was good average. Those were increased at the second cycle: the percentage of individual absorption was very good average, the percentage of classical completeness was very good average, and the percentage of classical absorption was still good average, respectively. Activities of the teacher at the first cycle was good average, and at the second cycle was very good average. Activitiesof students at the first cycle was good average, and increased at the second cycle into a very good average. The use of guided inquiry strategy improved student’s motivation. Improving student’s motivation was indicated by increasing motivation with a good average at the first cycle to a very good average at the second cycle. This study concluded that the implementation of guided inquiry strategy improved motivation and learning achievement of students.